Behavioral research as physical enrichment for captive chimpanzees. Issue 4 (27th May 2016) - Hopper, Lydia M.; Shender, Marisa A.; Ross, Stephen R.
Abstract : In this study, we evaluated the potential for a behavioral research study, designed to evaluate chimpanzee decision‐making behavior, to also encourage increased activity in a group of zoo‐housed chimpanzees. For the behavioral study, the chimpanzees had to carry tokens to different locations such that they always had to travel farther to obtain a more‐preferred reward. We recorded the distance travelled by each subject in each of the three phases of the 15‐month study. By the final phase, the chimpanzees' rate of travel during test sessions was significantly higher compared to their baseline activity. Importantly, the chimpanzees' increase in locomotion was not dependent on their participation in the study; rate of travel was not correlated with number of tokens exchanged. However, the chimpanzees' activity returned to baseline within 2 hr of the 30‐min test sessions. This study emphasizes the role that research can have in providing enrichment, the importance for long‐term enrichment plans, and the essential need to evaluate the impact of research on animal participants, just as we evaluate the efficacy of enrichment strategies. Zoo Biol. 35:293–297, 2016. © 2016 Wiley Periodicals, Inc.